2015
DOI: 10.1021/acs.biomac.5b00567
|View full text |Cite
|
Sign up to set email alerts
|

The Interplay of Disulfide Bonds, α-Helicity, and Hydrophobic Interactions Leads to Ultrahigh Proteolytic Stability of Peptides

Abstract: The contribution of noncovalent interactions to the stability of naturally occurring peptides and proteins has been generally acknowledged, though how these can be rationally manipulated to improve the proteolytic stability of synthetic peptides remains to be explored. In this study, a platform to enhance the proteolytic stability of peptides was developed by controllably dimerizing them into α-helical dimers, connected by two disulfide bonds. This platform not only directs peptides toward an α-helical conform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 52 publications
1
19
0
Order By: Relevance
“…A noteworthy example was the self-assembly of β-sheet peptides into amyloid-β protein by inter-strand hydrophobic interactions, which exhibited extreme resistance toward intracellular proteases (Barz et al, 2018 ). Inspired by this, the Wu group reported that crosslinked helix dimers can be constructed by two disulfide bonds for ultrahigh proteolytic stability (Chen et al, 2015 ). To overcome the instability of disulfide linkage under the intracellular reducing condition, Wuo et al developed more judicious covalent bonds like bis-triazole linkers (Wuo et al, 2015 ) and hexafluoroisopropanol-based bisthioether crosslinkers (Wuo et al, 2018 ; Chen et al, 2019 ) ( Figure 5B ).…”
Section: Potential Development Direction Of Anoplinmentioning
confidence: 99%
“…A noteworthy example was the self-assembly of β-sheet peptides into amyloid-β protein by inter-strand hydrophobic interactions, which exhibited extreme resistance toward intracellular proteases (Barz et al, 2018 ). Inspired by this, the Wu group reported that crosslinked helix dimers can be constructed by two disulfide bonds for ultrahigh proteolytic stability (Chen et al, 2015 ). To overcome the instability of disulfide linkage under the intracellular reducing condition, Wuo et al developed more judicious covalent bonds like bis-triazole linkers (Wuo et al, 2015 ) and hexafluoroisopropanol-based bisthioether crosslinkers (Wuo et al, 2018 ; Chen et al, 2019 ) ( Figure 5B ).…”
Section: Potential Development Direction Of Anoplinmentioning
confidence: 99%
“…More specifically, these structural modifications may ameliorate peptide solubility and bioavailability in biological media while also improving its serum stability toward endogenous peptidases and proteases (Gentilucci et al, 2010). The latter has shown to effectively improve the resident time of the peptide at the localized biological site for extended duration of action, thereby increasing its therapeutic index (Chen et al, 2015). Moreover, reduction of immunostimulatory effects and offtarget toxicity associated with non-selective and low affinity binding to receptor targets has facilitated the translation of lead sequences into effective peptide-based anti-cancer drugs (Luther et al, 2017).…”
Section: Rationale For Backbone Modifications In Cell Penetrating/tarmentioning
confidence: 99%
“…The proteolytic stability of the heterodimer (t1/2 = 13 h) depends directly on its evolutionarily derived secondary structure considering that the sequence holds 24 potential proteinase K cleavage sites and that the parallel homodimers were degraded 39-fold more quickly (t1/2 < min). The interplay between α-helical conformation, disulfide bonds and interfacial hydrophobic interactions of dimeric peptides can be crucial components for high proteolytic stability [42]. Distinctin, for example, a heterodimeric pore-forming peptide found in skin secretions of the frog Phyllomedusa distincta, is also resistant to proteolysis [39,40].…”
Section: Stabilitymentioning
confidence: 99%